Pengaruh Kepemimpinan Transaksional,Beban Kerja, Lingkungan Kerja Terhadap Kinerja Karyawan di PT. Viet Star Cirebon - Alin Wianda; Ardian Rahman; Puspita Rahmadani (Penerbit Jurnal Indonesia, 2026)
Employee performance plays an important role in supporting organizational goal achievement because it reflects the level of productivity and work effectiveness. Optimal performance is essential for manufacturing companies to remain competitive and sustain their operations. This study aims to examine the effect of transactional leadership, workload, and work environment on employee performance at PT. Viet Star Cirebon. Data were collected through a survey using structured questionnaires distributed to employees of PT. Viet Star Cirebon using a non probability sampling technique. Data analysis was conducted using multiple linear regression, accompanied by validity and reliability tests. The results show that transactional leadership has a positive and significant effect on employee performance, workload has a negative and significant effect on employee performance, and the work environment has a positive and significant effect on employee performance. These findings indicate that improving leadership quality, managing workload appropriately, and creating a supportive work environment are crucial in enhancing employee performance at PT. Viet Star Cirebon.